Gas Chromatography-Mass Spectrometry Analysis of the Aqueous Fraction of Caralluma dalzielii for Antischistosomal Activity - Mohammed, Mahmood; Umar, Yahaya Abdullahi; Vantsawa, Philip Anthony; Dibal, Deborah Madi; Dahiru, Sani (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2024)
Schistosomiasis remains a public health burden in tropical and subtropical countries with 90% of the cases occurring in Africa. Treatment of the disease has relied on a single drug parziquantel (PZQ) for more than one generation, thus increasing the possibility of drug resistance. The majority of the pharmaceutical industry rely on medicinal plants as their raw materials. Caralluma dalzielii belonging to the family Asclepiadaceae is well known for its Antischistosomal activity. This work is aimed to determine the phytochemical profile of the aqueous fraction of C. dalzielii using GC-MS analysis. Using conventional techniques, GC-MS Analysis was performed on GC-MS-QP2010 Plus Shimadzu. The component spectrums were compared to the database of known component spectrums kept in the GC-MS library. Eleven bioactive compounds with antihelminthic activity were identified by GC-MS analysis, originating from distinct peaks. These compounds include Octadecanoic acid, 1, E-8, Z-10-Hexadecatriene, 9, 12, Octadecanoic acid, Diethylene, and Ricinoic acid. The aqueous fraction of C. dalzielii's GC-MS profile showed the existence of metabolites with significant pharmacological characteristics. Hence, the plant extract's antischistosomal actions may be caused by the presence of these phytochemical metabolites.